Investigating the association of physical and psychological problems with the levels of interleukin-1 and -6 in COVID-19 patients - Bahadori-Birgani, Galia; Molavynejad, Shahram; Rashidi, Mahbobe; Amiri, Fereshteh; Maraghi, Elham; Dashtbozorgi, Bahman; Ulhaq, Zulvikar Syambani; Alizadeh-Attar, Gholamreza (Frontiers in Psychiatry, 2023)
Introduction: The Covid-19 virus spreads at a high rate, exerting many physical, mental and psychological effects on patients. Patients with Covid-19 have been reported to have high levels of interleukin 1 and interleukin 6. Therefore, this study was conducted to determine the association of physical, mental, and psychological problems with the levels of interleukin-1 and -6 in Covid-19 patients. Methodology: This is cross-sectional descriptive-analytical research on 121 Covid-19 patients selected using simple random sampling method. The patients were hospitalized in university hospitals affiliated to Ahvaz Jundishapur University of Medical Sciences and Amir al-Momenin Hospital. Data collection tools included the Depression Anxiety Stress Scale (DASS), a demographic questionnaire, and a checklist of physical problems. Blood sampling was also done to perform an ELISA test and measure the level of interleukin-1 and -6. Data were analyzed using SPSS ver. 22. Results: The average age of the 121 patients participating in this study was 53.31 ± 14.09. A direct and statistically significant correlation was observed between body temperature on the first day and interleukin 1 level. A statistically significant negative correlation was observed between blood oxygen saturation level and interleukin-1 and -6 on the first, third and fifth days. Shortness of breath and coughing had a statistically significant correlation with the level of interleukin 1 on the third and fifth days. A direct and statistically significant correlation was observed between body temperature on the first, third and fifth days and interleukin 6 level. Coughing on the third and fifth days had a statistically significant relationship with interleukin 6 level. No direct and nonsignificant statistical correlation was found between depression and stress and the serum level of interleukin 1, but a significant correlation was observed between anxiety and serum level of interleukin 1. Finally, the results showed that depression, anxiety and stress had a direct and statistically significant correlation with the serum level of interleukin 6.Given the relationship between interleukin-1 and -6 and most physical and psychological problems, level of the inflammatory biomarkers interleukin-1 and -6 can be used to estimate the severity of physical and psychological symptoms in Covid-19 patients.